ANALISIS PASAR TRADISIONAL DI WILAYAH KECAMATAN BUKO KABUPATEN BANGGAI KEPULAUAN - Ambojo, Jufriyadi; Palampanga, Anhulaila M.; Ichwan, Mohammad (Katalogis, 2019)
The purpose of this study is to determine and analyze the conditions of traditional markets based on the level of comfort, security and competition between traders. To know and analyze the process of distribution of goods and services at the level of traders in traditional markets and to find out and analyze the steps taken by the government related to the management of traditional markets. This research uses descriptive statistical analysis technique that is frequency analysis. The population of this research is traders or sellers in the traditional markets of Buko District, Banggai Kepulauan Regency, both retail and wholesale traders as much as 83 people. The sampling technique uses saturated or census sampling. The results showed that the condition of traditional markets in Buko sub-district according to the majority of traders were in a comfortable, safe condition with a healthy level of competition. The process of distribution of goods from traders to consumers is felt quite good based on the acquisition of a mean value of 3.50. The Banggai Kepulauan Regency Government through Law No. 3 of 2008 concerning protection, empowerment of traditional markets and structuring of modern markets is trying to make improvements. This is based on the acquisition of the mean value of 3.42.